Romance e realidade na ficção brasileira contemporânea - Juliana Santini (Estudos de Literatura Brasileira Contemporânea)
This work is a reflection on the representation of real in the novel Inferno provisório, by Luiz Ruffato, considering proposals by Claudio Magris on modern form of novel and its possible transformations in last decades. The aim is questioning the way by which aesthetic project of this novel embodies a deep point of view of real, creating an ethic and critical principle of analysis on contemporary society.